Analysis of phytochemical constituent and biological significance of rhododendrons collected from capital of Laliguras, Laliguras municipality, Tehrathum district, Nepal - Subba, Bimala; Baral, Chahana Dhakal; Seling, Tank Raj; Sharma, Khaga Raj (Scientific World, 2023)
The largest genus of the Ericaceae family, Rhododendron includes an inspiring number of species. Some of which have been used in the treatment of various ailments such as diseases associated with heart, dysentery, diarrhea, detoxification, fever, constipation, bronchitis and asthma around the world including Nepal. However, systematic study on phytochemistry and pharmacology of Rhododendrons grown in the Capital of Laliguras, Laliguras Municipality, Tehrathum of Nepal is lacking. So this study was conducted to evaluate the antioxidant activity, α-amylase inhibition activity, total phenolic and flavonoid contents of Rhododendron arboretum and Rhododendron campanulatum from Laliguras Municipality, Tehrathum of Nepal. Plant extracts were prepared in methanol by cold percolation method. Phytochemical constituents were analyzed by following standard methods. Antioxidant activity was measured through 2, 2-Diphenyl-1-Picrylhydrazyl assay. Total phenolic and flavonoid content were estimated using Folin–Ciocalteau and aluminum chloride method respectively. Alpha amylase inhibition assay was carried out by starch iodine method. Phytochemical screening of methanolic extract of flower and leaf of R. arboretum and leaves of R. campanulatum displayed the presence of different chemical constituents such as flavonoids, polyphenols, terpenoids, saponins and quinins. Samples showed dose-dependent radical scavenging and α-amylase inhibition activity. Radical scavenging activity and α-amylase inhibition activity of the methanolic extracts of different parts of R. arboretum and R. campanulatum ranged from 19.46 to 95.88% and 13.23 to 68.44% respectively. Flower extracts of R. arboreum showing the strongest radical scavenging activity and α-amylase inhibition with IC50 values 33.61 and 443.44 μg/mL respectively. Among the tested samples, flower extract of R. arboretum showed the strongest antioxidant activity, alpha amylase inhibition activity and contained the highest amount of total phenolic and flavonoid content.